Inorganic nitrogen uptake by Black Sea microplankton in connection with hydro chemical conditions. - Krivenko, O V; Lukjanova, A L (PANGAEA, 1994)
To study inorganic nitrogen uptake rates by microplankton in the Black Sea the first 15N-experiments were carried out in August-September 1990 and in November 1991. In surface waters nitrate uptake rates varied from 5.7 to 28.5 nM/l/h in summer and from 1.9 to 7.8 nM/l/h in autumn. In both seasons maximal and minimal rates were observed in frontal zones of shelf/slope areas and in open waters, respectively. In summer average nitrate uptake rate per unit of particulate organic nitrogen was 0.0037 1/h for all stations. In autumn it varied from 0.0007 1/h in the central part of the sea to 0.0033 1/h in the slope near the southeastern Crimean coast. In autumn ammonium uptake rate varied from 7.1 to 22.2 nM/l/h and from 0.0025 to 0.00094 1/h. Ammonium uptake correlated linearly with nitrate uptake, with new production being 22-36% of total summary nitrate and ammonium uptake. There was a linear correlation between nitrogen uptake and chlorophyll a concentrations in the Black Sea. In the water column in autumn both nitrate and ammonium uptake decreased as chlorophyll a concentration diminishes with depth.
(Table 2) Rates of nitrate and ammonium uptake, concentrations of particulate organic nitrogen and carbon, and dissolved nitrate and ammonium in waters of the Black Sea August-September 1990 and November 1991
Keywords: Ammonium; Ammonium uptake rate; Ammonium uptake rate, specific; Archive of Ocean Data; ARCOD; Black Sea; Carbon, organic, particulate; Chlorophyll a; Colorimetry; Date/Time of event; DEPTH, water; Element analyser CHN; Nitrate; Nitrate uptake rate; Nitrate uptake rate, specific; Nitrogen, organic, particulate; Professor Vodyanitskiy; PV32; PV32-10; PV32-15; PV32-16; PV32-17; PV32-9; PV35; PV35-18; PV35-21; PV35-23; PV35-25; PV35-26; PV35-27; PV35-28; Radiometric counting of introduced radioisotopes; Water sample; WS